P5 ACCESSORY PATHWAYS HIGH–DENSITY MAPPING IN WOLFF–PARKINSON–WHITE SYNDROME. (18th May 2022) - Conti, M; Serra, P; Befacchia, G; Santarelli, F; Benvenuto, M; Fabiani, D; Napoletano, C
Abstract: Wolff–Parkinson–White syndrome is a common condition characterized by atrioventricular accessory pathways (AP), which can be asymptomatic or can be responsible for atrioventricular reentrant tachycardia or rapid conduction of atrial fibrillation to the ventricles: for this reason, patients are referred for catheter ablation procedures. Although success rates of ablation are >95%, late recurrences can occur in 2–21% of cases mainly depending on the anatomical position. Current approaches remain suboptimal, and when failures occur, they may be due to technical difficulties such as poor contact or catheter stability, inability to access the target site as well as mapping errors resulting in inaccurate location of the AP itself. High–density mapping represents an alternative approach to mapping arrhythmias since the collection of a high density of points allows pathway conduction to be mapped more efficiently. The use of a new software called open–window mapping proved to be reliable in the localization of AP and therefore in the determination of the effective ablation site. A 41–year–old male patient was referred to our Centre following the ECG finding of manifest ventricular preexcitation and short–lasting paroxysmal palpitations. In the Electrophysiology Lab, the diagnostic catheters were inserted with the "fluoroless" technique using the EnSite Precision™ mapping system (Abbott): the ECG and the endocavitary electrograms were indicative of a right Parahissian accessory pathway. The mapping was performed with a multipolar catheter (Advisor™ HD Grid). Once the location of the pathway had been estimated, the roving acquisition interval (RAI) was set according to the expected position of atrial and ventricular electrogram. The RAI window was centered at this point and was opened in both directions (open window mapping) to fully include signals leading up to and traveling away from the AP. It accurately showed the location of the pathway just few millimeters from the Hissian potential. The baseline electrophysiological study revealed an effective antegrade refractory period (PREAP) of 320 msec. In isoproterenol, antegrade PREAP was reduced to 300 msec and inducibility of arrhythmias was not observed. Therefore, in consideration of the poor conductive properties and the non–inducibility of arrhythmias, as well as the anatomical site near the conduction system, it was decided not to proceed with the ablation due to the significant risk of atrio–ventricular block.